An online english course using a task-based language teaching: the teacher as an agent of choice - Emidio, Denise Elaine; Barbirato, Rita de Cássia (Universidade Estadual Paulista, 2016)
Since the advent of the new technologies, the language teaching came across to a virtual learning environment. In an attempt to consider the principles of the communicative approach (ALMEIDA FILHO, 2002, 2005, 2012) and the task-based language teaching (TBLT) (SKEHAN, 1996; XAVIER 1999, 2007; BARBIRATO 1999, 2005) an online English course was offered in the Moodle platform to students of technical, technological and Undergraduate courses from a Federal institution of technology. The theme chosen for the course was Inventors and Inventions and the thematic units contemplated aspects of Nikola Tesla’s and Leonardo da Vinci’s lives and inventions. The purpose of this article, therefore, is to present and discuss results derived from a doctoral research analyzing the teacher’s role in the preparation of thematic material based on tasks for the online English course in the Moodle. The data analysis pointed out to the very important role of the teacher in the challenges and choices along the process of the material elaboration.